Validity of periodontitis screening questions in a Brazilian adult population-based study - Renato Quirino RAMOS; João Luiz BASTOS; Marco Aurélio PERES
Abstract Population-based studies assessing self-reported periodontal questions in low-income countries are lacking, and therefore we aimed to assess the accuracy of self-reported periodontal items in Brazil. One thousand one hundred and forty adults from Florianópolis, Brazil, had their periodontium clinically examined, and responded to the following self-reported items on periodontal conditions: Question (Q)1, Do you have any wobbly teeth?; Q2, Do your gums usually bleed?; and Q3, Has your dentist ever told you that you have gum disease? Periodontitis was defined as: a. ≥ 6.0 mm periodontal pocket and ≥ 4.0 mm clinical attachment loss in the same tooth, in at least one tooth (PD1); or b. ≥ 6.0 mm periodontal pocket and ≥ 4.0 mm clinical attachment loss, not necessarily in the same tooth (PD2). Sensitivity (SN) and specificity (SP) were calculated, and analyses were stratified by socioeconomic status and time since last dental visit. Scores were generated in order to determine the accuracy of the whole set of items. Receiver operating characteristic (ROC) curves were plotted. Prevalence of clinically diagnosed periodontitis was 2.6% (95%CI = 1.7-4.0%) for PD1 and 3.8% (95%CI = 2.7-5.3%) for PD2. Prevalence of self-reported periodontitis varied between 2.7 (Q2) and 22.0% (Q3). SN and SP ranged between 0.0-60.0% and 73.3-98.6%, respectively; Q1 showed the highest accuracy (140.8%) followed by Q3 (140.0%). The combined score of the three self-reported items did not improve accuracy estimates; the areas under the ROC curves were 0.70 and 0.68 for PD1 and PD2, respectively. The accuracy of self-reported items was low, and further studies are needed in order to develop valid and reliable periodontitis screening questions for population-based studies.